From Moab to Selalang: Reading Ruth's conversion in the mirror of Iban women's narratives - Pekuwali, John Riwu (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
This study interprets the narrative of Ruth's conversion in the Old Testament as a hermeneutical model for understanding the faith experience of Dayak Iban women in Selalang, Malaysia, particularly through the story of Ibu Lega. Conversion is not viewed merely as a formal change of religion, but as a complex relational, cultural, and spiritual process. Using a narrative and intertextual hermeneutic approach, this research explores how conversion emerges from experiences of loss, vulnerability, and relational love. Ibu Lega, who chose to remain in the Longhouse after her husband's death to care for her in-laws, created a space for the growth of Christian faith through her steadfastness. In this context, conversion does not reject culture but transforms it into a new form of embodied spirituality lived in daily practices. Like Ruth, Ibu Lega’s path to faith did not pass through institutional religion, but through embodied acts of love and sacrifice. This narrative challenges dogmatic colonial mission models and proposes an alternative theology of conversion that is contextual, relational, and intercultural. As a communal spiritual space, the Longhouse becomes a locus for liberating faith transformation that honors local cultural wisdom.